Effects of systemically administered abaloparatide, an osteoanabolic PTHrP analog, as an adjuvant therapy for spinal fusion in rats. Issue 1 (25th November 2020) - Arlt, Heike; Besschetnova, Tatiana; Ominsky, Michael S.; Fredericks, Douglas C.; Lanske, Beate
Abstract: Background: Abaloparatide is a parathyroid hormone receptor agonist that increases bone formation and reduces vertebral and nonvertebral fracture risk in women with postmenopausal osteoporosis. Animal studies indicate abaloparatide stimulates vertebral bone formation and enhances bony bridging and biomechanical stability of fracture calluses. Aims: The current study is evaluating the potential utility for abaloparatide as an adjunct therapy for spinal fusions. Material and Methods: The effects of 14 or 28 days of daily subcutaneous injections of abaloparatide (20 μg/kg/d) or vehicle were evaluated in 32 male Sprague‐Dawley rats starting 1 day after noninstrumented posterolateral fusion (PLF) with bone autograft. Fusion mass microarchitecture was analyzed by micro‐computed tomography (micro‐CT) and serum markers of bone formation and bone resorption were evaluated. Motion segments were scored in a blinded manner as fused or unfused by postmortem radiography and manual palpation. Results: Abaloparatide‐treated rats showed higher bone formation (serum osteocalcin) at day 14 and 28 compared with vehicle controls, without increases in the bone resorption marker serum TRACP‐5b. Micro‐CT showed greater trabecular number in fusion masses from the abaloparatide group vs vehicle controls at day 14. Manual palpation and radiography indicated no fusions in either group at day 14, whereas 25% of vehicle‐treated rats and 50% of abaloparatide‐treated rats had bilateral fusion at day 28. Discussion and Conclusion: In summary, this rat PLF model showed that abaloparatide treatment was associated with higher levels of the bone formation marker osteocalcin, improved fusion mass architecture, and a non‐ significant 2‐fold higher fusion rate compared with vehicle. Abstract : 3D micro‐computed tomography images of motion segments showing lack of spinal fusion at day 14, and successful spinal fusion at day 28.